(E)‐4‐[(2‐Carbamoylhydrazinylidene)methyl]‐3‐hydroxy‐5‐hydroxymethyl‐2‐methylpyridin‐1‐ium nitrate. (12th June 2013) - Novaković, Sladjana B.; Bogdanović, Goran A.; Leovac, Vukadin M.; Rodić, Marko V.; Vojinović‐Ješić, Ljiljana S.; Ivković, Sonja
Abstract : The title compound, C9 H13 N4 O3 + ·NO3 −, is the first structurally characterized Schiff base derived from semicarbazide and pyridoxal. Unusually for an unsubstituted semicarbazone, the compound adopts a syn conformation, in which the carbonyl O atom is in a cis disposition relative to the azomethine N atom. This arrangement is supported by a pair of hydrogen bonds between the organic cation and the nitrate anion. The cation is essentially planar, with only a hydroxymethyl O atom deviating significantly from the mean plane of the remaining atoms (r.m.s. deviation of the remaining non‐H atoms = 0.01 Å). The molecules are linked into flat layers by N—H...O and C—H...O hydrogen bonds. O—H...O hydrogen bonds involving the hydroxymethyl group as a donor interconnect the layers into a three‐dimensional structure.